Satellite Cells: Regenerative Mechanisms and Applicability in Muscular Dystrophy - Gustavo Torres de Souza; Rafaella de Souza Salomão Zanette; Danielle Luciana Aurora Soares do Amaral; Francisco Carlos da Guia; Claudinéia Pereira Maranduba; Camila Maurmann de Souza; Ernesto da Silveira Goulart Guimarães; João Vitor Paes Rettore; Natana Chaves Rabelo; Antônio Márcio Resende do Carmo; Fernando de Sá Silva; Carlos Magno da Costa Maranduba (Hindawi Limited, 2015)
The satellite cells are long regarded as heterogeneous cell population, which is intimately linked to the processes of muscular recovery. The heterogeneous cell population may be classified by specific markers. In spite of the significant amount of variation amongst the satellite cell populations, it seems that their activity is tightly bound to the paired box 7 transcription factor expression, which is, therefore, used as a canonical marker for these cells. Muscular dystrophic diseases, such as Duchenne muscular dystrophy, elicit severe tissue injuries leading those patients to display a very specific pattern of muscular recovery abnormalities. There have been works on the application of precursors cells as a therapeutic alternative for Duchenne muscular dystrophy and initial attempts have proven the cells inefficient; however later endeavours have proposed solutions for the experiments improving significantly the results. The presence of a range of satellite cells populations indicates the existence of specific cells with enhanced capability of muscular recovery in afflicted muscles.